Implementasi Model Pembelajaran Problem-Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa SMP Negeri 1 Cikidang Kabupaten Sukabumi: Penelitian - Rani Nurhayati Rosida (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mathematical critical thinking skills are essential competencies that need to be developed in students so they can effectively face real-life challenges. This study aims to explore the implementation of the Problem-Based Learning (PBL) model in enhancing students' mathematical critical thinking abilities at SMP Negeri 1 Cikidang, Sukabumi Regency. A qualitative approach with a field study method was used, and the research was conducted directly at the school. Data were collected through interviews with teachers and students, classroom observations, and document analysis. The data analysis process included data reduction, data presentation, and drawing conclusions. The findings indicate that the application of the PBL model in mathematics learning was carried out through several stages, including problem identification, data collection, data analysis, and solution presentation, all of which actively involved students. There was a significant improvement in students' mathematical critical thinking abilities after the implementation of the PBL model, particularly in analyzing, evaluating, and logically concluding in solving mathematical problems. The results from tests and observations supported the improvement in both quantitative and qualitative aspects. Therefore, the Problem-Based Learning model is proven to be effective in enhancing students' mathematical critical thinking skills at SMP Negeri 1 Cikidang.